DIVERSIFIKASI RUMPUT LAUT DAN GARAM MENJADI “SOAP BAR & BATH SALT” SEBAGAI PELUANG EKONOMI KREATIF MASYARAKAT PESISIR DI KOTA TARAKAN - Novi Luthfiyana; Heni Irawati; Stephanie Bija; Mukmainna Mukmainna; Gita Lia Rosalinda; Ricky Febrinaldy Simanjuntak (Universitas Mataram, 2022)
Tarakan is an area located in the tropical sea area, North Kalimantan. One of the leading commodities that have the potential to be developed is Eucheuma cottonii seaweed. In addition, krosok salt in this city also has the opportunity to be used as a diversified product that has added value. This commodity opens up creative economic opportunities for the coastal community of Tarakan City. Eucheuma cottonii contains bioactive, antioxidant, and antibacterial compounds. Krosok salt contains minerals that are beneficial to the body. This activity aims to provide insight into appropriate science and technology through counseling and training to the community. This training is expected to open up business opportunities and improve the welfare of families, especially coastal communities. The method used consists of 3 stages. First, socialization and counseling regarding E. cottonii seaweed and krosok salt use. Second, training and mentoring participants. The third stage, evaluation and monitoring related to the obstacles experienced during the manufacture of soap bars and bath salts. The results of this community service activity provide new insights and information about the benefits of E. cottonii seaweed and krosok salt. These two commodities can be processed into soap bar and bath salt products. Through this activity, the community gains new knowledge in applying science and technology. The community is also more skilled in diversifying products besides the food sector. Soap bar products from E. cottonii seaweed and bath salt from krosok salt can be made on a household scale, so the process is straightforward. This step is one of the strategies for an independent and creative economy. Through this activity, coastal communities are expected to be more creative and economically independent by manufacturing soap bars and bath salt products.